The Pesticides Trust - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The Pesticides Trust is an environmental charity established in includes in its membership a wide range of interests - environmental, food and consumer, farming and horticulture, conservation, wildlife, medical, health and safety and development...